Impact of the updating of clinical guidelines for RSV bronchiolitis on the use of diagnostic testing and medications in tertiary hospitals in Colombia (2022)
ABSTRACT: Introduction: the incidence of Respiratory Syncytial Virus (RSV) infection and their variability in the clinical management, make this disease a candidate for monitoring adequate use of resources. The objective of this study was to evaluate the impact of the updating of clinical guidelines for RSV bronchiolitis on the use of diagnostic testing and medications in tertiary hospitals in Colombia. Methods: we performed a cross-sectional study, evaluating the frequencies of drug prescription and medical tests, before (January-December 2016) and after (January to December 2019) of updating and dissemination of a new protocol for the treatment of RSV bronchiolitis in two tertiary hospitals in Colombia. Results: a total of 108 patients with RSV bronchiolitis were included. The demographic characteristics and clinical manifestations were similar in both groups. The length of hospital stays was similar in both groups. We did not find statistically significant differences in the frequency of medical tests. There was a decrease in the use of salbutamol (67.3% pre-protocol vs 51.8% post protocol; P < .01). There were also significant reductions in the use of nebulized hypertonic saline solution (91.6% vs 82.6% P = 0.004). Conclusion: our results demonstrate that the updating of clinical guidelines for RSV bronchiolitis was effective, as it achieved decreases in the use of bronchodilators and nebulized hypertonic saline solution. It is necessary to continue developing new strategies targeted to increase adherence to guidelines and evaluate the impact on the use of resources.